ANALISIS HASIL BELAJAR IPA PADA SISWA KELAS V DI SD NEGERI 3 PETALING - Rizka Lela Agustina (Universitas Negeri Medan, 2021)
Abstract : The purpose of this study was to find out the understanding of the concept of science in living things for class V SD Negeri 3 Petaling. The research method used in this research is quantitative description. Data collection techniques in this study were tests, interviews and documentation. The data obtained were then analyzed using the mean, standard deviation and percentage. The results of this study indicate that the average understanding of science concepts in class V energy source material at SD Negeri 3 Petaling is included in the moderate criteria of 50%. This is evident from the results of the study that the percentage of students' understanding of science concepts from five indicators which include: identifying the human breathing apparatus, identifying the workings of the human respiratory apparatus, explaining the function of the human respiratory apparatus, explaining disorders of the human respiratory apparatus, explaining how the respiratory apparatus works man.Keywords: Understanding of Science Concepts, Energy SourcesAbstrak : Tujuan penelitian ini untuk mengatahui pemahaman konsep IPA pada materi makhluk hidup kelas V SD Negeri 3 Petaling. Metode penelitian yang digunakan dalam penelitian ini adalah kuantitatif deskripsi. Teknik pengumpulan data dalam penelitian ini tes, wawancara dan dokumentasi. Data yang diperoleh kemudian dianalisis menggunakan mean, simpangan baku dan persentase. Hasil penelitian ini menunjukkan bahwa rata-rata pemahaman konsep IPA pada materi sumber energi kelas V SD Negeri 3 Petaling termasuk dalam kriteria sedang 50%. Hal ini terbukti dari hasil penelitian peroleh persentase pemahaman konsep IPA peserta didik dari lima indikator yang meliputi: mengidentifikasi alat pernafasan manusia, mengidentifikasi cara kerja alat pernafasan manusia, menjelaskan fungsi alat pernafasan manusia, menjelaskan gangguan pada alat pernafasan manusia, menjelaskan menjelaskan cara kerja alat pernafasan manusia.Kata kunci : Pemahaman Konsep IPA, Sumber Energi